1999
DOI: 10.1086/501675
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Prevalence Surveys in a Tertiary-Care Center: Trends in Nosocomial Infection Rates, Device Utilization, and Patient Acuity

Abstract: Despite apparent increases in the severity of illness of our patients, overall rates of nosocomial infection remained stable during a decade of study. Rates of nosocomial bloodstream infection increased, in parallel with National Nosocomial Infection Surveillance System data. We found repeated prevalence surveys to be useful in following trends and rates of infection, device utilization, and abnormal laboratory values among patients at our institution. Such methodologies can be valuable and low-cost components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 18 publications
(10 reference statements)
2
74
1
1
Order By: Relevance
“…Studies conducted in western European countries showed that the prevalence of HAI in hospitals was between 3.5% and 8.5% (9)(10)(11)(12)(13)24). Ten annual prevalence surveys were conducted in a 900-bed tertiary-care hospital in the USA; however, the prevalence of patients with HAIs showed no significant increase during the 10-year period, although the rate of bloodstream infection significantly increased (25).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in western European countries showed that the prevalence of HAI in hospitals was between 3.5% and 8.5% (9)(10)(11)(12)(13)24). Ten annual prevalence surveys were conducted in a 900-bed tertiary-care hospital in the USA; however, the prevalence of patients with HAIs showed no significant increase during the 10-year period, although the rate of bloodstream infection significantly increased (25).…”
Section: Discussionmentioning
confidence: 99%
“…Catheter-associated urinary tract infection)CA-UTI) or nosocomial UTIs ,also known as health care associated UTIs.CA-asymptomatic bacteriuria (ASB) as the presence of significant bacteriuria in a patient without symptoms referable to the urinary tract, and CA-UTI as the presence of significant in a patient with symptoms or signs referable to the urinary tract [1].Nosocomial UTIs(comprised mostly of ASB),up to 97 % of which are associated with instrumentation of the urinary tract, are the most common nosocomial infections worldwide [2,3],and account for up to 40% of nosocomial infections in U.S.hospitals each year [4].UTI is also the leading cause of infections in long term-care facilities(LTCFs) and most of these are catheterassociated [5].Urinary catheterization is very prevalent in hospitals and LTCFs and its use appears to be increasing at least in the hospitals [6].Approximately 15% to 25% of patients in general hospitals have a catheter inserted at some time during their stay [4,7].Most of these patients are catheterized for only 2 to 4 days [8].The duration of catheterization is the most important factor for the development of CA-bacteriuria [8]. Other risk factors for CA-bacteriuria include the lack of systemic antimicrobial therapy, femalesex, meatal colonization with uropathogens, microbial colonization of drainage bag, catheter insertion outside operating room, catheter care violations, absence of us of a drip chamber, rapidly fatal underlying illness, older age, diabetes, and elevated serum creatinine at the time of catheterization [7].…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors for CA-bacteriuria include the lack of systemic antimicrobial therapy, femalesex, meatal colonization with uropathogens, microbial colonization of drainage bag, catheter insertion outside operating room, catheter care violations, absence of us of a drip chamber, rapidly fatal underlying illness, older age, diabetes, and elevated serum creatinine at the time of catheterization [7].…”
Section: Introductionmentioning
confidence: 99%
“…1 An estimated 30 million urinary catheters are used annually in the United States. Prevalence of catheter use among hospitalized patients ranges from 16% to 33% 2,3 and is even higher (67%-76%) in critically ill patients. 4,5 But up to onethird of patients may not have an appropriate indication for a catheter to be used.…”
mentioning
confidence: 99%
“…4,5 But up to onethird of patients may not have an appropriate indication for a catheter to be used. 3,[6][7][8] Inappropriate catheter use occurs because of convenience, misunderstanding of necessity, and lack of clear orders for catheter removal 9 or the physician's lack of awareness of the catheter's presence. 8 More than 500 000 catheter-associated urinary tract infections (CAUTIs) occur each year in the United States alone.…”
mentioning
confidence: 99%